Application of an ant colony metaphor for network address management in MANETs (2009)
Address management is a critical process in a computer network. The ownership of a network address is a requisite for every node willing to make part of a network. In adhoc networks, address management is a particularly tough challenge, because of their dynamically changing topology, and the sort of events that occur in their environment. This article proposes a solution to the aforementioned problem, involving the self-organization and emergency principles governing the behavior of social insect colonies. In particular, the solution uses the organization and behavior principles present in ant colonies. © 2009 IEEE.